Raltitrexed (Tomudex) versus standard leucovorin-modulated bolus 5-fluorouracil: Results from the randomised phase III Pan-European Trial in Adjuvant Colon Cancer 01 (PETACC-1). - Popov, I; Carrato, A; Sobrero, A; Vincent, M; Kerr, D; Labianca, R; Raffaele Bianco, A; El-Serafi, M; Bedenne, L; Paillot, B; Mini, E; Sanches, E; et al. (2008)
OBJECTIVES: PETACC-1 assessed if raltitrexed is non-inferior to 5-fluorouracil and leucovorin for relapse-free survival (RFS) and overall survival (OS) in adjuvant stage III colon cancer. METHODS: Non-inferiority required both HR for RFS and OS<1.25 at 1-sided alpha=0.05. Patients (1921) were randomised to six cycles of 5-FU/LV (n=969) or eight cycles of raltitrexed (n=952). We report the final results in 993 eligible patients who started and completed the allocated treatment (489 5-FU/LV and n=504 Raltitrexed) of whom respectively 146 and 148 died, respectively. RESULTS: The trial closed prematurely when 17 (1.9%) raltitrexed-related deaths were reported. Haematological and gastrointestinal toxicities were more frequent with 5-FU/LV, liver toxicities with raltitrexed. Raltitrexed was stopped for toxicity in 13.2% and 5-FU/LV in 8.5%. Sixty-day mortality was 9% versus 7%. With 4.1 years median follow-up, the HR for RFS was 1.16 (90% CI 0.99-1.37) and that for OS was 1.01 (90% CI 0.84-1.23). CONCLUSION: The trial failed to demonstrate non-inferiority of raltitrexed. FUNDING: Free drugs and financial support from AstraZeneca.